Application of 3D-printing extrusion technology in foundry production - N. K. Tolochko; A. A. Andrushevich; P. N. Vasilevsky; P. S. Chugaev (Литьë и металлургия, 2019)
A brief review of the additive technologies used for producing the foundry forming tooling is carried out. The peculiarities of using extrusion 3D-ptinting technology for producing the foundry forming tooling in comparison with other additive technologies are considered. The possibilities to produce the foundry forming tooling from clay viscous-flowing materials using extrusion 3D-ptinting technology are demonstrated experimentally.